Association of systemic inflammatory factors with clinical outcomes in patients with autoimmune encephalitis at different clinical stages - Jin, Bo; Duan, Yiqun; Wu, Wenxin; Hu, Jing; Wu, Xiaoyan; Zhang, Sheng; Wu, Huadong; Aung, Thandar (Frontiers in Immunology, 2025)
ObjectiveOur study aimed to explore the association of systemic inflammatory factors in relations to disease severity of the cell surface antibody-mediated autoimmune encephalitis (AE) across various stages.MethodsWe retrospectively analyzed patients with AE from two hospitals between October 2016 and December 2023. Systemic inflammatory factors were measured at admission and discharge. Disease severity and prognosis were assessed using the clinical assessment scale for autoimmune encephalitis (CASE), and multivariate logistic regression analysis was used to identify associated risk factors.ResultsA total 83 patients were enrolled. The CASE score and the modified Rankin Scale score were positively correlated at admission, discharge and follow-up (r=0.937, P < 0.001; r=0.910, P < 0.001; r=0.972, P < 0.001). Multivariate logistic regression analysis revealed that a higher systemic immune-inflammation index (SII) at admission (OR=27.617, 95% CI: 1.060–719.699, P=0.046) and an elevated platelet-to-lymphocyte ratio (PLR) at discharge (OR=11.373, 95% CI: 1.166–110.893, P=0.036) were independent risk factors for severe disease at admission and discharge, respectively. Additionally, a high neutrophil-to-platelet ratio (NPR) at either admission (OR=10.384, 95% CI: 2.036–52.958, P=0.005) or discharge (OR=5.714, 95% CI: 1.189–27.455, P=0.036) was associated with poor prognosis.ConclusionsSII and PLR were associated with disease severity, while NPR was a consistent predictor of poor long-term outcomes. These findings highlight the value of systemic inflammatory factors in monitoring disease progression and guiding treatment decisions in patients with AE mediated by cell surface antibody.